PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN BERBASIS WEB UNTUK REKOMENDASI MOBIL BEKAS PADA SHOWROOM JAYA RAHARJA MOTOR MENGGUNAKAN METODE MOORA - Sopiyan Apandi; Aldi Adam Fanrian (Informatika: Jurnal Teknik Informatika dan Multimedia, 2025)
This study addresses the challenge of providing accurate and efficient used car recommendations at Jaya Raharja Motor showroom, which previously relied on conventional methods. A web-based decision support system was developed using the MOORA (Multi-Objective Optimization on the Basis of Ratio Analysis) method and the Agile Scrum approach. The system successfully ranked 21 used car alternatives, with the Vellfire ZG (A17) achieving the highest score of 0.09149, making it the top recommendation.